Aminophenolates of aluminium, gallium and zinc: Synthesis, characterization and polymerization activity. (27th March 2017) - Basiak, Dariusz; Dobrzycki, Łukasz; Socha, Paweł; Rzepiński, Patryk; Plichta, Andrzej; Bujnowski, Krzysztof; Synoradzki, Ludwik; Orłowska, Natalia; Ziemkowska, Wanda
Abstract : Complexes containing aminophenolate ligands are considered as very efficient initiators of ring‐opening polymerization (ROP). Our systematic studies of the reactions of two selected aminophenols, 2‐[( p ‐tolylamino)methyl]‐4‐(2, 4, 4‐trimethylpentan‐2‐yl)phenol (L'H2 ) and 2‐cyclohexylaminomethyl‐4‐methylphenol (L″H2 ), with alkyl compounds of aluminium, gallium and zinc resulted in the formation of a variety of products depending on the type of metallic centre and alkyl groups bonded to metal atoms. New trinuclear aluminium complexes (Me5 Al3 (L′)2 (1 ) and Me5 Al3 (L″)2 (2 )), monomeric aluminium ( t Bu2 Al(L'H) (3 ) and t Bu2 Al(L″H) (5 )) and gallium ( t Bu2 Ga(L'H) (4 ) and t Bu2 Ga(L″H) (6 )) compounds, and dinuclear gallium (Et2 Ga(L″H)·Et3 Ga (7 )) and zinc ( t BuZn(L″H)]2 (8 )) complexes were isolated and characterized. The molecular and crystal structures of 7 and 8 were determined on the basis of an X‐ray diffraction study. Polymerization tests showed that only three complexes (6 –8 ) had activity in the ROP of ε ‐caprolactone, whereas 1 –5 were inactive in ROP. Abstract : Reactions of two selected aminophenols with alkyl compounds of aluminium, gallium and zinc resulted in the formation of a variety of products, which were studied as initiators of ring‐opening polymerization.